2016
DOI: 10.1177/1521025116666539
|View full text |Cite
|
Sign up to set email alerts
|

Noncognitive Factors and College Student Success

Abstract: Farrington and colleagues developed a model that contends that academic mindsets, academic perseverance, learning strategies, social skills, and academic behaviors affect academic success. This study tests a modified version of this model with first-year students (n ¼ 1,603) at a large, ethnically diverse, urban university. The hypothesized structural model had acceptable fit, with minor modifications. The direct effect on academic performance of academic mindset was strong, of academic perseverance was modest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 39 publications
1
48
0
2
Order By: Relevance
“…Grit was positively associated with measures of academic performance, such as GPA, GCSE, ACT scores, science and language scores, as well as with more behavioral outcomes, such as school motivation, attendance and behavior, academic conscientiousness, satisfaction with school/college, decreased rule violation, and performance on the ADT task (e.g. Bowman et al, 2015;Farruggia et al, 2016). It also displayed positive associations with mastery approach goal orientation (Akin & Arslan, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Grit was positively associated with measures of academic performance, such as GPA, GCSE, ACT scores, science and language scores, as well as with more behavioral outcomes, such as school motivation, attendance and behavior, academic conscientiousness, satisfaction with school/college, decreased rule violation, and performance on the ADT task (e.g. Bowman et al, 2015;Farruggia et al, 2016). It also displayed positive associations with mastery approach goal orientation (Akin & Arslan, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…A number of studies found that each facet of grit is associated with different variables. Grit-PE was negatively correlated with academic maladjustment (Hwang et al, 2017) and positively associated with GPA (Bowman et al, 2015;Farruggia et al, 2016), achieved grade (Weisskirch, 2016), motivation, academic self-efficacy, and time management (Farruggia et al, 2016). It also correlated positively with college satisfaction, faculty-student interaction, and co-curricular engagement, while Grit-CI was related to less intent to change careers (Bowman et al, 2015), procrastination, time and study environment management strategies (Wolters & Hussain, 2015).…”
Section: Oriol Miranda Oyanedel and Torres (2017)mentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple researchers have ascertained that more conscien-tious students earn higher college GPAs (Bauer & Liang, 2003;Lounsbury et al, 2005). In addition, Farruggia, Han, Watson, Moss, and Bottoms (2016), after talking to participants enrolled as first-year students at a large, ethnically diverse, urban university, established a correlation of the noncognitive variables of academic mindsets, academic perseverance, learning strategies, social skills, and academic behaviors with academic success. They also found that academic performance was most strongly related to an academic mindset followed by the will to persevere (grit).…”
Section: Noncognitive Predictive Assessmentmentioning
confidence: 99%
“…One other study attempted to test a version of the CCSR model as a whole. Farruggia, Han, Watson, Moss, & Bottoms (2016) tested a version of the hypothesized CCSR model with an ethnically diverse sample of college students, rather than adolescents which was intended by the CCSR model. Overall, Farruggia and colleagues found some support for the hypothesized model, but some of their findings did not support the model.…”
Section: The Whole Modelmentioning
confidence: 99%